Wachsen durch wen? Stadtentwicklungsstrategien in Bremen und Leipzig im Umgang mit Migration - Kühn, Manfred; Bernt, Matthias (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
The article examines the urban development strategies of Bremen and Leipzig with regard to their dealing with migration. The key questions of the article are as follows: Which target groups of migrants prefer urban development policies in order to achieve growth goals? To what extent is there a change of perspective on migration from problems to potentials of urban development? Our empirical results show that both cities focus primarily on the immigration of young and highly skilled workers. Both cities also rely on the immigration of students and try to keep them after graduation. However, this orientation is difficult to put into practice, because in both cities the number of job opportunites for highly qualified people is limited. The importance of immigration from abroad, which is the most increasing growth segment, was initially less well perceived by both cities and has only gained more strategic importance in recent years. International immigration is simultaneously perceived as potential and problem in the urban development concepts of both cities. The article discusses the dilemmas of cities in dealing with migration. These include, in particular, the lack of control capacity in terms of migrant selection and recruitment, a "dual regime" between growth and integration policies, and often a selective focus on subgroups of actual immigration.
Keywords: Migration; Strategic city planning; Regeneration; Bremen; Leipzig